A PARAMETRIC STUDY ON CONTROL OF FLOW SEPARATION OVER AN AIRFOIL IN INCOMPRESSIBLE REGIME - Prabhu, L; Srinivas, J (IIUM Engineering Journal, 2018)
This paper presents the effects of airfoil geometry on flow separation behavior and obtains the transition patterns at a specific angle of attack. A strong adverse pressure gradient field is observed at the leading edge of the airfoil, and it results in a flow detachment. Leading edge flow separation is studied along with the variation of skin friction coefficient over the airfoil. Novelty in the approach is the development of a hybrid control scheme to delay the flow separation with blowing/suction of air (termed active control) over the airfoil together with the tapping of flow from the pressure side as in a classical passive control procedure. The active controller delays the flow separation, while the passive controller is used to reduce the drag coefficient significantly and increases the total performance of an airfoil. The effectiveness of these controls is examined by varying the control parameters including blowing/suction velocity, the position of the slot in terms of percentage of chord and size of the slot. All the numerical simulations are carried out using ANSYS-Fluent software. A surrogate model is also developed to predict the aerodynamic characteristics conveniently without much computational effort. The outcome of this study reveals that the blowing/suction velocity has a higher influence in delaying the flow separation. ABSTRAK: Kertas ini membentangkan tentang kesan geometri aerofoil pada perubahan pemisah aliran udara dan memperoleh bentuk peralihan pada darjah yang tepat. Terdapat tekanan kuat yang tidak sesuai pada kawasan kecerunan di hujung hadapan permukaan aerofoil, dan ini menyebabkan aliran udara terpisah. Pemisah aliran udara pada hujung hadapan ini dikaji bersama koefisien geseran pada permukaan aerofoil. Pendekatan baru pada kaedah ini adalah berkaitan pembangunan skim kawalan hibrid bagi melengahkan aliran pemisah udara melalui tiupan/sedutan udara (kawalan aktif) ke atas aerofoil bersama ketukan pada aliran dari tepi tekanan seperti mana prosedur klasik kawalan pasif. Kawalan aktif ini melengahkan aliran pemisah udara, sebaliknya kawalan pasif telah digunakan bagi mengurangkan koefisien penangguhan dengan ketara dan menambahkan jumlah prestasi aerofoil. Keberhasilan kawalan-kawalan ini dikaji dengan mengubah parameter kawalan termasuk kelajuan tiupan/sedutan udara, posisi slot berdasarkan peratusan garis temu dan saiz slot. Semua simulasi-simulasi numerikal ini dijalankan menggunakan perisian Ansys-Fluent. Model pengganti turut dibangunkan untuk menjangka ciri-ciri aero-dinamik dengan mudah tanpa usaha pengiraan yang banyak. Keputusan kajian ini mendedahkan tentang kelajuan tiupan/sedutan udara berpengaruh besar dalam melambatkan pemisahan aliran udara.